OPTIMASI KEUNTUNGAN PRODUK KERIPIK SINGKONG MENGGUNAKAN METODE BRANCH AND BOUND DAN ALGORITMA GENETIKA PADA GNP SNACK - Sarif Hasan; Yohanes Anton Nugroho (Spektrum Industri, 2020)
GNP Snack company has problems in making raw material inventories which are sometimes not enough for 0.5 tons of cassava chips to fulfill demand. This will affect the production process carried out every day. Production needs per day 1 - 1.5 tons of production of cassava chips. The company benefits of GNP Snack are not optimal because it only produces an average profit per month of Rp. 2,000,000 therefore the right formula is needed to overcome this problem using the Branch and Bound Method and the Genetic Algebra Method. The calculation results from the branch and bound method show an increase in profits in December 2018 of Rp. 2,018,992 to Rp. 2,531,467 or a 25% increase, in January 2019 amounting to Rp. 2,247,488 to Rp. 4.247.620 or an increase of 89%, and in February 2019 Rp. 1,290,661 to Rp. 1,299,020 or experiencing a 1% increase and the results of calculations using the genetic algorithm method show an increase in profits in December 2018 of Rp. 2,018,992 to Rp. 2,555,477 or a 27% increase, in January 2019 Rp. 2,247,488 to Rp. 2,655,551 or an increase of 18%, and in February 2019 Rp. 1,290,661 to Rp. 2,810,316 or 118% increase.